Analysis of the Influence of Mudharabah Financing on the Profitability of Indonesian Islamic Banks - Kumaidi, Kumaidi (LPPM Universitas Terbuka, 2024)
The purpose of this study is to explain that mudharabah financing has a big role in increasing the profits of Islamic banks in Indonesia. This research uses a descriptive qualitative medote type of literature study which aims to collect and analyse various literatures related to the subject under study. Descriptive analysis can be used to provide an overview of the data collected. The data collection process consists of a number of systematic steps taken to ensure that the information collected is correct. Firstly, the researcher selects appropriate sources. Secondly, relevant keywords were used. Thirdly, each source found was thoroughly checked. Fourth, relevant data was organized and categorized for additional analysis. Some research results that have been presented from several studies can be concluded that mudharabah financing has a good and significant effect on the profitability of Islamic banks, especially Bank Syariah Indonesia. These results help the management of Islamic banks develop more innovative and sustainable financing policies and products.